Strategies for Strengthening Character Education Through the Integration of Islamic Values: The Role of Teachers as Role Models in the Context of Contextual Learning - Sevia Diana Safitri (AFKARINA: Jurnal Pendidikan Agama Islam, 2024)
This research focuses on the integration of character values in the Islamic Religious Education curriculum and the role of teachers as exemplary models in shaping students' character. The purpose of this study is to explore how contextual teaching approaches and consistency of teacher behavior can affect the internalization of character values by students at Nurul Jadid Junior High School. This study uses a qualitative approach with a case study method, where data is collected through in-depth interviews, participatory observations, and document analysis. The collected data was analyzed using an interactive model from Miles and Huberman, which included the stages of data reduction, data presentation, and conclusion drawn/verification. The results of the study show that the integration of character values such as honesty, responsibility, tolerance, and cooperation in the curriculum, as well as the role of teachers as role models, is very effective in shaping students' character. The implications of this study confirm the importance of developing contextual teaching methods and consistency of teacher behavior to support more effective character education. This research makes a significant contribution to the literature on character education, especially in the context of Islamic Religious Education.